The functional significance of residual yolk in lizards. Issue 2 (7th December 2022) - Guo, Kun; Wang, Cai-Feng; Du, Yu; Qu, Yan-Fu; Braña, Florentino; Ji, Xiang
Abstract: Residual yolk is assumed to be an important source of energy and nutrients during early life in nonmammalian amniotes. Available data show that the mean size of residual yolk is far smaller in lizards than in turtles, snakes, crocodiles, and birds, raising a question of whether residual yolk is of functional significance in lizards. Here, we compared data from 26 lizard species with those from other nonmammalian amniotes to test the hypothesis that residual yolk is functionally less significant in species producing more fully developed offspring. In our sample, species mean offspring water contents ranged from 73% to 84% of body wet mass; species mean proportions of carcass dry mass, fat-body dry mass, and residual yolk dry mass to offspring dry mass ranged from 84% to 99%, 0% to 5.0%, and 0% to 14.4%, respectively. Lizards are, on average, more fully developed at hatching or birth than snakes, as revealed by the fact that the mean proportion of carcass dry mass to body dry mass and offspring water contents were both higher in lizards than in snakes. We conclude that the functional significance of residual yolk during early life is generally less evident in lizards. Even in the lizards where residual yolk is of potential functional significance, this portion of yolk contributes little, if any, to postembryonic growth. Future work could usefully collect data across a wider spectrum of reptile taxa to establish a precocial–altricial continuum and test the hypothesis that species with a smaller amount of residual yolk are closer to the precocial end of the continuum.